ANALISIS TRANSMISI HARGA TANDAN BUAH SEGAR (TBS) DARI PABRIK KELAPA SAWIT (PKS) Ke PETANI SWADAYA DI KELURAHAN SOREK SATU KECAMATAN PANGKALAN KURAS KABUPATEN PELALAWAN - Ermi Tety; Evy Maharani; Muhammad Setiawan (Program Studi Pendidikan Ekonomi Universitas Riau, 2012)
The purpose of this research is to investigate marketing channels, marketingmargins of TBS oil palm and to know the part that received by farmers, thecorrelation or relationship between the prices of oil palm paid by PKS withthe prices received by swadaya farmers, as well as the effect of price changesof oil palm at PKS standard with the price of swadaya farmers standard atSorek Satu District, Pangkalan Kuras Subdistrict. This study was conducted fromAugust 2010 to January 2011. The method that the researcher used was surveymethod. The Sampling of the research was 32 swadaya farmers with the ageof palm trees between 10-15 years done by purposive sampling, whereas for tradersand PKS done by snow ball. Based on the results of one marketing channels inSorek Satu and the average of marketing margins of time series data for theyear 2010 was Rp. 245,25, while the share of farmers is 87%. The correlationvalue of the price from swadaya farmers standard with the price PKS standardwas 0.976 and the price transmission based on the coefficient regression valueof b1 was 0,884.